Matchlock gun - Edmonds, Walter Dumaux ([S.l.] Dodd, 1941)
In 1756, during the French and Indian War in upper New York state, ten-year-old Edward is determined to protect his home and family with the ancient, and much too heavy, Spanish gun that his father had given him before leaving home to fight the enemy.